Applications for inertial sensors in elite level half pipe snowboarding - Harding, J.; Mackintosh, C.; Martin, D.; Rosmond, D.; Dowlan, S.; James, D. (Australian Institute of Physics 17th National Congress, 2006)
Sport managers need to understand the core social identity that athletes, coaches, and judges share in order to place the group`s culture at the centre of the technological innovation narrative. Whilst Hardman`s Pyramid of Constraints is focused on useful evaluative levels, the rigidity of the hierarchical process presents challenges for its use for a sport such as snowboarding, as the model prioritises either structural or moral dimensions as most important. In this study the aesthetic aspects of snowboarding emerged as the primary dimension of concern for community members. We consequently forward a more fluid conceptual model of the structural, aesthetic, and moral components of a sport that is void of any hierarchical process and where the prioritisation of the mostimportant dimension (structural, aesthetic, or moral) is established by the sporting community itself. This conceptual reframing results from understanding what makes a sport distinct from other groups, and why this is importantto members through a social identity approach. In sports where style and freedom are key values of a sport group, the aesthetic dimension is arguably more important than moral or structural dimensions; hence the issues with the rigid structure of Hardman`s framework. The key contribution of this study is to place the views of the sport community and its stakeholders as central to the technological innovation process. This is not to privilege athletes, coaches and judges as the only stakeholders who need to be consulted, but to develop a structured implementation process, designed to increase the chances that technologies can be integrated in ways that acknowledge the norms, characteristics and cultural intricacies of the sport in question. Further research analysing proposed technological changes in other sports will provide opportunities to refine the fluid conceptual model offered by this study and determine its transferability to other sporting contexts.